The role of somatic factors in early childhood and adolescent psychosomatic disorders (Bangladesh Journal of Medical Science, 2023)
Objective. This study aimed to establish practical evidence of the leading role of somatic factors in psychosomatic health disorders in the early stages of the mental development of children and adolescents.Materials and methods. An interview method was used to obtain complete and reliable historical data for children and youth who applied for primary medical care. In addition, an anonymous questioning method was implemented. It allowed gathering of a reliable database of basic information on the psychosomatic health of children and adolescents in the Western European region. A study enrolled a sample of 1000 children, including 498 girls and 502 boys, aged 13 to 18 years.Results and Discussion. Psychosomatic pathologies were detected in 54% of cases, of which 63% were female. The influence of somatic factors on psychosomatic pathology progression was found to be greater in the early stages of mental development.Conclusion. The study’s findings may serve as a primary basis for understanding the role of somatization factors on psychosomatic disorders in children and adolescents in the early stages of mental development. The study also highlights the need to enhance the methodological basis for preventing psychosomatic disorders in children and adolescents.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 687-694